The Role of Advanced Cardiac Imaging in Monitoring Cardiovascular Complications in Patients with Extracardiac Tumors: A Descriptive Review - Annamaria Tavernese; Valeria Cammalleri; Rocco Mollace; Giorgio Antonelli; Mariagrazia Piscione; Nino Cocco; Myriam Carpenito; Carmelo Dominici; Massimo Federici; Gian Paolo Ussia (Journal of Cardiovascular Development and Disease)
Cardiac involvement in cancer is increasingly important in the diagnosis and follow-up of patients. A thorough cardiovascular evaluation using multimodal imaging is crucial to assess any direct cardiac involvement from oncological disease progression and to determine the cardiovascular risk of patients undergoing oncological therapies. Early detection of cardiac dysfunction, particularly due to cardiotoxicity from chemotherapy or radiotherapy, is essential to establish the disease’s overall prognostic impact. Comprehensive cardiovascular imaging should be integral to the clinical management of cancer patients. Echocardiography remains highly effective for assessing cardiac function, including systolic performance and ventricular filling pressures, with speckle-tracking echocardiography offering early insights into chemotoxicity-related myocardial damage. Cardiac computed tomography (CT) provides precise anatomical detail, especially for cardiac involvement due to metastasis or adjacent mediastinal or lung tumors. Coronary assessment is also important for initial risk stratification and monitoring potential coronary artery disease progression after radiotherapy or chemotherapeutic treatment. Finally, cardiac magnetic resonance (CMR) is the gold standard for myocardial tissue characterization, aiding in the differential diagnosis of cardiac masses. CMR’s mapping techniques allow for early detection of myocardial inflammation caused by cardiotoxicity. This review explores the applicability of echocardiography, cardiac CT, and CMR in cancer patients with extracardiac tumors.